Occupational health and safety performance measurement in healthcare sector using integrated multi criteria decision making methods - Korkusuz, Ammar Yasir; Inan, Umut Hulusi; Ozdemir, Yavuz; Basligil, Huseyin (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2020)
It is essential to measure the OHS performance quickly, objectively and realistically; in order to determine the effects of legislative changes and new OHS applications; to compare performance of a company with others in the same sector and to determine the OHS level of subcontractors. The methods in the literature measure OHS performance for single enterprise by long-term observations with high expertise. There was no OHS performance measurement method that can measure performance of multiple enterprises in a short period. In this study, new method of measuring OHS performance for healthcare sector was developed by using integrated MCDM methods. OHS indicators were first identified and weighted by AHP method. To obtain performance indices, PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluations) and GRA (Gray Relational Analysis) methods were used. Two performance indices by two methods were compared and consistency of results is examined. Moreover, the correlation between OHS performance indices and hospitals' other features (hospital type, ISO 9001 certificate, year of hospital establishment, year of OHS unit establishment) was analyzed. Implementation of the developed method was carried out in 27 hospitals in Izmir and Istanbul.
Keywords: Multi-criteria decision making; Occupational health and safety; OHS performance measuremen safety indicators; OHS in healthcare sector; RISK-EVALUATION; FUZZY AHP; MANAGEMENT-SYSTEMS; FAILURE MODE; ISO 9001; QUALITY; COMBINATION; SELECTION; FMEA; Engineering